2004
DOI: 10.22621/cfn.v118i4.54
|View full text |Cite
|
Sign up to set email alerts
|

A Mapping of the Present and Past Forest-types of Prince Edward Island

Abstract: Our aim was to produce maps showing the distribution on Prince Edward Island of five forest-types previously identified from a TWINSPAN analysis of ground flora data collected at 1200 sampling points in a field survey. For this purpose we had available two databases: one on the composition of the tree canopy of 82,957 forest stands, as determined by photointerpretation of a 1990 aerial photographic survey of the island; the other on the drainage properties of the same stands from a published soil survey. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…A well-known limitation of classification studies is that they simplify the gradient of forest conditions found in an ecosystem (Sobey and Glen 2004). Hence, such classifications often result in a few "ideal" forest types, which are in fact rarely observed in the field.…”
Section: Advantages and Disadvantages Of The Classification Approachmentioning
confidence: 99%
“…A well-known limitation of classification studies is that they simplify the gradient of forest conditions found in an ecosystem (Sobey and Glen 2004). Hence, such classifications often result in a few "ideal" forest types, which are in fact rarely observed in the field.…”
Section: Advantages and Disadvantages Of The Classification Approachmentioning
confidence: 99%
“…still exist. A projection by Sobey and Glen (2004) of the pre-European settlement forest of P.E.I. indicates that the province was mostly covered by upland hardwood forest, a stand type that composes only 21.7% of its present forested area.…”
Section: Discussionmentioning
confidence: 99%
“…Only small relicts of the original vegetation of the island still exist. A projection by Sobey and Glen (2004) of the pre-European settlement forest of Prince Edward Island indicates that the island was mostly covered by upland hardwood forest, a stand type that occurs on only 21.7% of the forested area of the island today.…”
Section: Discussionmentioning
confidence: 99%
“…(Pinaceae), Pinus strobus L. (Pinaceae), Thuja occidentalis L. (Cupressaceae), and Fraxinus americana L. (Oleaceae). These tree species are now restricted to a few small stands on PEI, but formerly they were much more widespread (Sobey and Glen 2004).…”
Section: Discussionmentioning
confidence: 99%